Los proyectos de aula encaminados a desarrollar buenos hábitos alimenticios en los niños de 4 a 5 años del salón kínder del centro de educación inicial Lev Vigotsky del cantón Chone - García Robles, Daniela Alejandra (2016)
Food is one of the basic physiological needs of children, in order to keep the body in its proper functioning. And it is the role of educators to establish correct eating patterns in children, since they alone cannot be formed in these areas without adults. In Ecuador, it is common to see children demanding and throwing tantrums at their parents to receive junk food. And the parents for lack of dedication and patience yield to their demands. But what if, instead of telling them not to eat certain foods and begging them to eat the nutrients, they are instilled with the benefits of healthy eating? Would it change their eating habits?.........